Adenosine A2A receptor upregulation in human PMNs is controlled by miRNA-214, miRNA-15, and miRNA-16 - Heyn, Jens Michael; Ledderose, Carola; Lindner, Holger A. (Shock, 2012)
Immunosuppressive signaling via the adenosine A2A receptor (A2AR) is an important pathway to control inflammation. In immune cells, expression levels of A2ARs influence responsiveness to inflammatory stimuli. However, mechanisms driving expressional changes of A2ARs are still largely elusive. In the current study, we have investigated the impact of microRNAs (miRNAs) on A2AR expression in human polymorphonuclear leukocytes (PMNs) and T cells. Bioinformatic analyses and reporter gene assays revealed that A2AR expression is controlled by miRNA-214, miRNA-15, and miRNA-16. We detected all three miRNAs in both human PMNs and T cells. However, in PMNs, up to 10-fold higher levels of miRNA-16 and miRNA-214 were detected as compared with T cells. Upon in vitro stimulation, no significant expressional changes occurred. Expression levels of all three miRNAs strongly differed between individuals. A2AR expression also exhibited significant differences between PMNs and T cells: In PMNs, more than a 60-fold increase was seen upon LPS stimulation, whereas in T cells only a 2-fold increase was observed upon anti-CD3/CD28 activation. The extent of A2AR upregulation in PMNs strongly differed between individuals (from less than 10-fold to more than 100-fold). In PMNs, the increase in A2AR mRNA expression upon stimulation was inversely correlated with the expression levels of miRNA-214, miRNA-15, and miRNA-16 (R = −0.87, P < 0.0001); no correlation was found in human T cells. These results indicate that individual miRNA profiles gain important influence on A2AR expression regulation in PMNs upon stimulation. Determination of miRNA expression levels may help to identify patients with an increased risk for severe inflammation.